Virtual Reality: An Innovative Tool in Destinations’ Marketing - Rainoldi, Mattia; Driescher, Veronika; Lisnevska, Alina; Zvereva, Daria; Stavinska, Anna; Relota, Jennifer; Egger, Roman (The Gaze: Journal of Tourism and Hospitality, 2018)
Virtual reality (VR) is a fast-developing technology with a broad range of use. The tourism industry, more specifically destinations, may benefit from its potential in the near future. By using VR in its marketing strategy, destinations have a substantial influence on the information search process and the decision-making process of potential tourists. Tourists can experience the destination, its atmosphere and possible emotions beforehand. Thus, they can create a more detailed destination image and realistic expectations of their visit. This transfers them into a better position to decide whether or not to visit a destination. This experimental study takes a closer look into a destination’s promotional material by analysing and comparing a self-designed brochure with an existing VR video of the city of Dubrovnik, Croatia. A total of 101 experiments were conducted at Fachhochschule Salzburg and UniparkNonntal. The research shows that VR transforms the information search experience into a faster, more interactive, and more detailed process compared to traditional promotional material. The results can be beneficial for destinations to understand how relevant using VR for tourism promotion is. The Gaze: Journal of Tourism and Hospitality Vol.9 2018 p.53-68